Ethnicisation of Democratic Dividends in Nigeria and Its Implications for Good Governance and Nation-Building - Azeez, Ademola; Olaleye, I. Oluseyi; Fatokun, Olalekan Samuel (African Journal of Stability and Development (AJSD), 2025)
Since the return to democratic rule in Nigeria’s Fourth Republic, the allocation of democratic dividends has often mirrored ethnic affiliations. This development has sparked widespread concern about fairness, good governance, and the integrative promise of democracy. This study interrogates the ethnicisation of democratic gains, where policies and public resources—including projects and appointments—are disproportionately channelled towards ethnic groups with close ties to those in political power. Rather than being shaped by merit or national interest, state decisions increasingly reflect ethnically driven strategies designed to build local support and secure electoral advantage. Consequently, democracy becomes entangled in narrow loyalties, eroding national unity and weakening public trust. Anchored in a qualitative research approach and supported by multiple case studies, this paper examines the consequences of ethnic-based resource distribution on good governance and sustainable nation-building. It raises key questions: How does this pattern affect public service delivery? What meanings does democracy assume when filtered through ethnicity? And how might such practices alter the foundations of collective national identity? The study provides theoretical reflection and practical insight, recommending reforms to recentre democracy as a unifying enterprise for all Nigerians.